2019
DOI: 10.3390/biom9060246
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Profiling Reveals Virulence-Associated Proteins of Fusarium proliferatum during Interaction with Banana Fruit

Abstract: Secreted proteins are vital for the pathogenicity of many fungi through manipulating their hosts for efficient colonization. Fusarium proliferatum is a phytopathogenic fungus infecting many crops, vegetables, and fruit, including banana fruit. To access the proteins involved in pathogen–host interaction, we used label-free quantitative proteomics technology to comparatively analyze the secretomes of F. proliferatum cultured with and without banana peel in Czapek’s broth medium. By analyzing the secretomes of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Overall, and as expected, our differential secretome analysis of A. pullulans NBB 7.2.1 culture supernatants did not correlate well with the transcriptome results. This effect was expected as it had been similarly reported in other systems [47][48][49][50][51][52]. In general, protein and transcriptome levels do not seem to be highly correlated [53], which is likely due to the additional levels of regulation that determine protein levels (i.e., translation, post-translational modification, formation of complexes, degradation).…”
Section: A Pullulans Nbb 721 Secretome Analysis During Competition With F Oxysporum Nrrl 26381/cl57supporting
confidence: 70%
“…Overall, and as expected, our differential secretome analysis of A. pullulans NBB 7.2.1 culture supernatants did not correlate well with the transcriptome results. This effect was expected as it had been similarly reported in other systems [47][48][49][50][51][52]. In general, protein and transcriptome levels do not seem to be highly correlated [53], which is likely due to the additional levels of regulation that determine protein levels (i.e., translation, post-translational modification, formation of complexes, degradation).…”
Section: A Pullulans Nbb 721 Secretome Analysis During Competition With F Oxysporum Nrrl 26381/cl57supporting
confidence: 70%
“…To facilitate host colonization, plant pathogens secrete proteins to host compartments that modulate morphological changes in the host system and establish fungal infection (68)(69)(70).…”
Section: The Predicted Secretome and Effector Proteinsmentioning
confidence: 99%
“…Although these plant pathogenic fungi secrete a large number of proteins, only a small proportion of these proteins have been implicated to be effectively associated with fungal-plant interactions, i.e. effector proteins (68)(69)(70). Effector proteins can strongly inhibit the activity of host cellular proteases and allow pathogenic fungi to evade host defense mechanisms.…”
Section: The Predicted Secretome and Effector Proteinsmentioning
confidence: 99%
“…Secretome profiling and prediction have been used to identify SPs of many pathogens, including Tilletia horrida [ 10 ], Fusarium proliferatum [ 11 ], Tilletia indica [ 12 , 13 ], rose black spot [ 4 ], Trichoderma virens [ 14 ], Arbuscular mycorrhizal [ 15 ], and Puccinia striiformis f. sp. tritici [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…tritici [ 16 ]. In the banana fruit pathogen, F. proliferatum , 105 secretory proteins were predicted based on the pathogen proteome [ 11 ]. In Foc TR4 , 2235 SPs were identified in one study, although the specific data were not shown [ 17 ].…”
Section: Introductionmentioning
confidence: 99%